Random-pattern versus perforator-based adipocutaneous skin paddles for postoperative monitoring of free muscle flaps: a comparative retrospective cohort study - Nagel, Sarah Sophie; Thomas, Benjamin; Fischer, Sebastian; Diehm, Yannick; Ziegler, Benjamin; Bigdeli, Amir Khosrow; Schmidt, Volker-Jürgen; Kneser, Ulrich; Radu, Christian Andreas (Journal of plastic, reconstructive & aesthetic surgery, 2021)
Introduction - Free microvascular muscle flaps represent well-established reconstructive options for complex soft tissue defects. However, due to their lack of cutaneous capillary beds, they are difficult to monitor postoperatively. To this end, random and axial-pattern adipocutaneous skin paddles are often included. The objective of the study was to compare the impact of random-pattern versus perforator-based adipocutaneous skin paddles on operative efficacy and muscle flap safety. - Methods - Between August 2014 and July 2016, a total of 120 free muscle flaps were included in this retrospective monocentric cohort study. Based on their skin-paddle type, they were either grouped into a ‘perforator-based‘ (group Pb) or ‘random-pattern’ (group Rp) cohort. The electronic medical records and operative reports of all patients were subsequently reviewed and patient, defect, and flap characteristics of both groups were compared. The effect of the competing skin paddle types on the overall operative time, incidences of flap loss or microvascular complications, and total length of hospital stay were then assessed. - Results - Group Pb comprised 72 flaps, whereas 48 flaps constituted group Rp. Patient, defect, and flap characteristics were similar between both groups. Groups Pb and Rp were comparable regarding patient age (group Pb: 61 (10-90) vs. Rp: 59 (13-81), p=0.556), ASA (American Society of Anesthesiologists) class (group Pb: 3 (1-4) vs. Rp 3 (1-3), p=0.977), and comorbidities, summarized by the Charlson comorbidity index (CCI; group Pb: 1 (0-4vs. Rp: 1 (0-5), p=0.295). Both types of monitoring skin paddles were equally reliable. There was no significant difference in the mean operation time between both groups (group Pb: 373±122min vs. Rp: 342±84min, p=0.124). In-patient treatment after flap surgery and total length of hospital stay were significantly shorter in group Pb (group Pb: 24±10 days vs. Rp: 32±17 days, p=0.002 and group Pb: 39±15vs. Rp: 48±24, p=0.022). - Conclusion - Perforator-based skin paddles are a reliable tool for postoperative perfusion monitoring of free muscle flaps and help avoid additional surgical interventions as opposed to their random-pattern counterparts. Thus, the overall and postoperative length of hospital stay is significantly reduced.